2022
DOI: 10.31635/ccschem.021.202000733
|View full text |Cite
|
Sign up to set email alerts
|

Site-Selective Palladium-Catalyzed 1,1-Arylamination of Terminal Alkenes

Abstract: Many of the commonly used pharmaceuticals and biologically active natural products are nitrogencontaining compounds. Recently, the transitionmetal-catalyzed or the radical-mediated 1,2-carboamination of alkenes has been well explored to access amine scaffolds. However, synthetic strategies toward the 1,1-carboamination of alkenes are severely limited. Herein, we describe a method to achieve the 1,1arylamination using readily available building blocks enabled by palladium catalysis. This sequential three step-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Such techniques not only offer a nonclassical site-selectivity pattern in the olefin functionalization arena but also provide a palette of conceptually new tactics for our ever-growing synthetic arsenal . Despite the elegant advances realized in C–C , and C–heteroatom bond-forming reactions, the incorporation of two different heteroatom motifs across the olefin backbone with a 1,1-site-selectivity pattern still remains an underexplored, yet desirable, endeavor (Scheme ). , …”
mentioning
confidence: 99%
“…Such techniques not only offer a nonclassical site-selectivity pattern in the olefin functionalization arena but also provide a palette of conceptually new tactics for our ever-growing synthetic arsenal . Despite the elegant advances realized in C–C , and C–heteroatom bond-forming reactions, the incorporation of two different heteroatom motifs across the olefin backbone with a 1,1-site-selectivity pattern still remains an underexplored, yet desirable, endeavor (Scheme ). , …”
mentioning
confidence: 99%
“…Despite the wealth of synthetic tools available for 1,2- or 2,1-carboaminations, there is only a handful of reports on 1,1-carboamination, with most strategies relying on β-hydride elimination and subsequent reinsertion of the transition metal (Scheme B) . Such a strategy has proven successful for certain intramolecular reactions yet mostly unsuccessful for three-component intermolecular settings because of competing undesired migration of the transition metal, as has been documented in reports by the groups of Heck and Larock . Recently, Ellman and colleagues have expertly demonstrated that this issue could be addressed by employing directing groups; however, this curtails the generality of the substrate scope …”
mentioning
confidence: 99%
“…We next turned our attention to exploring the utility of carboamination products. Unlike previous 1,1-carboamination methods employing transition-metal catalysis, our carboamination technology can preserve the alkene functionality throughout the process, setting the stage for myriad of transformations. For example, epoxidation of 5l with m -chloroperoxybenzoic acid ( m CPBA) proceeded stereoselectively to furnish 7 (79% yield).…”
mentioning
confidence: 99%